2021
DOI: 10.1007/s10936-021-09807-x
|View full text |Cite
|
Sign up to set email alerts
|

The Case for Smiling? Nonverbal Behavior and Oral Corrective Feedback

Abstract: Oral Corrective Feedback is a widely used teaching strategy that has been found to help language acquisition. The factors that contribute to its effectiveness, however, remain elusive. In this study, the role of smiling during teachers' OCF provision is investigated in intact language classrooms by modifying the analytical framework developed by Lyster and Ranta (Stud Second Lang Acquis, 19(1):37-66, 1997), which determines OCF effectiveness by the success of the learner uptake. In addition to the feedback str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Kozic et al (2013) found no significant differences in visual communication and facial expressions between experienced and novice teachers. Ergül (2021) also found not all smiles will have a good effect on students. This finding can be explained by the semiotic perspective.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Kozic et al (2013) found no significant differences in visual communication and facial expressions between experienced and novice teachers. Ergül (2021) also found not all smiles will have a good effect on students. This finding can be explained by the semiotic perspective.…”
Section: Discussionmentioning
confidence: 99%
“…While deeply analysing the selected lectures in this study, we found that teachers' smiles were often deliberate. Ergül (2021) found that when teachers faked smile while providing feedback to a student, students were not positively influenced by the feedback.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Types of reactions to errors can include eyebrow raises, head movements, gaze, and facial expressions. Many studies point to the fact that bystander behavioral reactions to a person's mistake are commonly observable by the person, and able to positively influence the person's performance, both intentionally and unintentionally [38,43,105,145]. Jones et al [63] goes even further and finds that the behavioral change resulting from social feedback works in a similar fashion to reinforcement learning.…”
Section: In Summarymentioning
confidence: 99%